LINC02499, a novel liver‐specific long non‐coding RNA with potential diagnostic and prognostic value, inhibits hepatocellular carcinoma cell proliferation, migration, and invasion. Issue 6 (2nd March 2020) - Ma, Xiaoyun; Mo, Meile; Tan, Hui Juan Jennifer; Tan, Chao; Zeng, Xiaoyun; Zhang, Guoqiang; Huang, Dongping; Liang, Jun; Liu, Shun; Qiu, Xiaoqiang
Abstract : Aim: Liver‐specific non‐coding RNAs have been reported to play crucial roles in hepatocellular carcinoma (HCC). We investigated the possible biological performance of a novel liver‐specific long non‐coding RNA, LINC02499, in HCC. Methods: The association between LINC02499 expression and HCC was evaluated based on The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases, and then confirmed in a HCC cohort by quantitative real‐time polymerase chain reaction. The effects of LINC02499 on HCC cells were verified by gain‐ and loss‐of‐function assays. Pathway enrichment analyses were used to explore the potential mechanism of LINC02499 in HCC. Results: LINC02499 expression was remarkably decreased in HCC tissues compared to adjacent non‐tumor tissues based on TCGA ( P < 0.001) and GEO databases ( P < 0.001) and our HCC cohort ( P < 0.001). Decreased LINC02499 was also significantly associated with poorer overall survival in both the TCGA database ( P = 0.009) and our HCC cohort ( P = 0.002). Furthermore, the receiver operating characteristic analysis indicated that LINC02499 showed a good performance in HCC diagnosis (area under the curve = 0.879, P < 0.001), and both sensitivity and specificity were 83.8%. In addition, up‐ and downregulated LINC02499 significantly impacted proliferation, migration, and invasion abilities of HCC cells in vitro. Pathway enrichment analyses revealed that the potential target genes of LINC02499 were involved in "Complement and coagulation cascades" and "Butanoate metabolism" pathways. Conclusion: LINC02499 could be a potential novel diagnostic and prognostic biomarker for HCC patients, and it could exert a tumor suppressor role in the progression of HCC.